The impact of achievement goals on college students’ English performance—a moderated mediation model - Tan, Shaojie; Abd Samad, Arshad; Ismail, Lilliati (Public Library of Science, 2025)
The study investigated the relationship between learning engagement and achievement goals, and English performance among college students. With the increasing popularity of online teaching methods, exploring how different teaching modes (online and classroom teaching) might influence students’ learning outcomes is important. The researcher sought to understand how adopting different achievement goals such as mastery and performance-avoidance approaches could impact English performance and learning engagement. By examining this factor, the study aimed to provide insights into effective teaching strategies and interventions that could enhance students’ academic success in English language learning. The survey included 953 college students assessed using the Achievement Goal Questionnaire and Learning Engagement Scale. Their IELTS English scores were also recorded to study the relationship between learning engagement and achievement goals, and English performance. Additionally, the researcher utilized statistical analysis tools such as SPSS and the PROCESS Marco programme to explore the moderated mediation model and to uncover the complex relationships among the variables in the study. The results revealed that adopting a mastery approach positively influenced English performance, while the performance-avoidance approach negatively influenced English performance. Additionally, learning engagement partially mediated the connection between the mastery approach, performance-avoidance approach, and English performance. Teaching mode influenced the initial phase of the mediating effect between the mastery approach and English performance. More importantly, compared to online teaching, classroom teaching with a focus on mastery approach had a stronger predictive effect on learning engagement. Lastly, there was a moderated mediating effect between English achievement and the mastery approach, whereas the performance-avoidance approach showed a simple mediating effect on English achievement. The findings from this research could potentially inform educators and policymakers on how to optimize teaching practices to promote student engagement and improve English language proficiency.